2022
DOI: 10.18240/ijo.2022.03.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corvis ST tonometer with the updated software in glaucoma practice

Abstract: AIM: To evaluate the agreement of biomechanically corrected intraocular pressure (b-IOP) and central corneal thickness (CCT) measurements obtained with the updated Corvis ST tonometer versus Goldmann applanation tonometry (GAT) and optical-based corneal pachymetry (OB-CCT) in controls, patients with ocular hypertension (OHT) and primary open angle glaucoma (POAG). Additionally, we examined the differences in corneal deformation parameters provided by the updated Corvis ST among the three groups. METHODS: For e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…There was no publication bias found in most of the comparisons through Egger tests ( P >0.05), except for the analysis of HC-t in the POAG group ( P =0.040, Table 3). The result indicated that the study of Halkiadakis et al50 contributed to the publication bias, but its exclusion did not change the pooled result (Table 4).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…There was no publication bias found in most of the comparisons through Egger tests ( P >0.05), except for the analysis of HC-t in the POAG group ( P =0.040, Table 3). The result indicated that the study of Halkiadakis et al50 contributed to the publication bias, but its exclusion did not change the pooled result (Table 4).…”
Section: Resultsmentioning
confidence: 93%
“…A total of 1922 records were identified in the electronic databases, 95 of which were included in the systematic review and 31 in the meta-analysis. Eighteen of the 31 articles used ORA to investigate differences in corneal biomechanical parameters between glaucoma patients and normal controls,10,14,24–39 while 15 used CST 11,16,36,37,40–50. The procedure of the literature search and the reasons for exclusion are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to GAT and NCT, CST adequately accounted for corneal biomechanical properties and provided a more comprehensive performance for IOP assessment [6,11,13] . In a study by Halkiadakis et al [30] no correlation was found between CST-IOP and CCT in eyes with OHT, primary open angle glaucoma, or normal eyes. In the present study, CST-IOP and GAT-IOP showed better consistency in the OHT group, non-OHT group, and all subjects compared with NCT-IOP.…”
Section: Discussionmentioning
confidence: 83%
“…The results obtained from optical pachymetry were 549.5±36.4 µm on average, and those from Corvis ST-556.41.5 µm, without statistically significant difference. In conclusion, the authors assume that the measured values of IOP and pachymetry between GAT, optical pachymetry, and Corvis ST are comparable, which is useful especially at low and high values of CCT(13). In the Bulgarian literature there is a similar study by Z. Zlatarova and a team comparing the values of IOP and CCT measured with Goldman's applanation tonometry, ultrasound pachymetry, and Tonopachy NT-530P non-contact tonometer.…”
mentioning
confidence: 83%